Retrospective evaluation of breast cancer patients with five or more axillary lymph node involvement achieving 5-year overall survival - Yersal, Özlem; Yiğit, Mehmet; Meydan, Nezih; Barutca, Sabri (The European Research Journal, 2019)
Objectives: The aim of this study was to analyze high risk breast cancer patients with involvement of five or more axillary lymph nodes with an overall survival of at least five years, and to determine the predictive and prognostic factors by comparing patients by recurrence/metastases status retrospectively. Methods: From a total of 500 patients those were followed up in Adnan Menderes University, Medical Oncology department, 37 were eligible for the study; 23 were disease free and 14 had recurrence/metastases in the follow up period. The patients were analyzed, for demographical (such as age, menopausal status, obesity), anatomical and histological characteristics of tumor (primary tumor’s diameter, stage, grade, Ki-67, hormon receptors and Her-2 status), treatment modalities and prognosis. Results: Both number of metastatic lymph nodes and (metastatic/sampled) lymph node ratio were not significantly different between the recurrence-free and metastatic patients. In the recurrence-free patients both grade 3 (48% vs none, p = 0.03) and p53 negative tumors (64% vs 36%, p = 0.036) were significantly more than metastatic patients. Also in the recurrence free patients as compared to metastatic patients, adjuvant chemotherapy was applied more than 6 cycles (87% vs 43%, p = 0.004), the regimens included more taxane based regimens (91% vs 64%, p = 0.042), aromatase inhibitors were used higher (100% vs 75%, p = 0.019) and the period of tamoxifen treatment in switch regimens were shorter. Conclusion: The results of this study suggested that, high risk breast cancer patients with involvement of five and more nodes that have the predictive factors as grade 3 and/or p53 negative tumors are propably more responsive to adjuvant treatments. Chemotherapy of more than 6 cycles, administering taxane based regimens and aromatase inhibitors in the adjuvant regimens may favourably effect the prognosis.